Development Of Students' Ideological-Ideological Immunity Legal Grounds (Journal of Pedagogical Inventions and Practices, 2023)
In this article, the study of legal culture in the literature for the development of students' ideological-ideological immunity is highlighted, the author revealed the essence of the concepts of education, legal consciousness and legal culture based on the analysis of theoretical materials.